Use of email in a family practice setting: opportunities and challenges in patient- and physician-initiated communication - Virji, Ayaz (BioMed Central, 2006)
BACKGROUND: Electronic mail (email) has the potential to improve communication between physicians and patients. METHODS: We conducted two research studies in a family practice setting: 1) a brief, anonymous patient survey of a convenience sample to determine the number of clinic patients receptive to communicating with their physician via email, and 2) a randomized, controlled pilot study to assess the feasibility of providing health education via email to family practice patients. RESULTS: Sixty-eight percent of patients used email, and the majority of those (80%) were interested in using email to communicate with the clinic. The majority also reported that their email address changed less frequently than their home address (65%, n = 173) or telephone number (68%, n = 181). Forty-two percent were willing to pay an out-of-pocket fee to have email access to their physicians. When evaluating email initiated by the clinic, 26% of otherwise eligible patients could not participate because they lacked email access; those people were more likely to be black and to be insured through Medicaid. Twenty-four subjects agreed to participate, but one-third failed to return the required consent form by mail. All participants who received the intervention emails said they would like to receive health education emails in the future. CONCLUSION: Our survey results show that patients are interested in email communication with the family practice clinic. Our feasibility study also illustrates important challenges in physician-initiated electronic communication. The 'digital divide' – decreased access to electronic technologies in lower income groups – is an ethical concern in the use of email for patient-physician communication.